(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Dyakonov G. V. Psychological and pedagogical research dialogue and reflection in learning and thinking. The article discusses the features of dialogue and reflection in cognition, thinking and learning. It reveals a multifaceted relationship of dialogue and reflection phenomena and analyzes their role in cognitive and mental processes. The nature and phenomenology of dialogue and reflection are considered from the standpoint of different approaches: psycholinguistic, psycho-pedagogic, social psychology, general psychology, experimental psychology and existential-ontological psychology.